Characterization and functional analysis of chicken dsRNA binding protein hnRNPU. (January 2023) - Hu, Xifeng; Wu, Xiangdong; Ding, Zhen; Chen, Zheng; Wu, Huansheng
Abstract: In mammals, heterogeneous ribonucleoprotein U (hnRNPU), also named as nuclear matrix protein-nuclear scaffold attachment factor (SAFA), was originally identified as a DNA/RNA interactor protein. It has been reported that human hnRNPU facilitates IFN-β generation after vesicular stomatitis virus (VSV) infection. Nevertheless, the role of chicken hnRNPU (chhnRNPU) in IFN-β regulation as well as in infectious bursal diseases virus (IBDV) replication is still unclear. Here, we found that chhnRNPU inhibits IFN-β production via interacting with MDA5 and MAVS, and facilitates IBDV replication via associating with genomic dsRNA of IBDV. Firstly, chicken hnRNPU (chhnRNPU) was widely expressed in different tissues of chickens and was distributed in the nucleus of DF-1 cells. Overexpression of chhnRNPU significantly suppresses IFN-β promoter activities induced by MDA5 and MAVS. Additionally, immunoprecipitated by dsRNA antibodies, which followed LC-MS analysis demonstrate that chhnRNPU is a partner of viral genomic dsRNA. chhnRNPU is translocated from nucleus to cytosol to co-localize with replication complex of IBDV after IBDV infection. Over-expression of chhnRNPU significantly promotes IBDV replication, which was determined by western blotting, qRT-PCR and TCID50 assay. Furthermore, knock down chhnRNPU by siRNA remarkably facilitates IFN-β production, and inhibits IBDV proliferation. These data collectively reveal that chhnRNPU positively regulates IBDV replication via negatively regulating IFN-β response. Highlights: Chicken hnRNPU was majorly located in the nucleus Chicken hnRNPU negatively regulate interferon β production Chicken hnRNPU facilitates IBDV replication via interacting with dsRNA of IBDV